Nasojejunal Feeding Is Safe and Effective Alternative to Feeding Jejunostomy for Postoperative Enteral Nutrition in Gastric Cancer Patients - Deepjyoti, Kalita; Bannoth, Srinivas; Purkayastha, Joydeep; Borthakur, Bibhuti B.; Talukdar, Abhijit; Pegu, Niju; Das, Gaurav (South Asian Journal of Cancer, 2020)
Background and Aim Carcinoma of the stomach is one of the leading causes of mortality worldwide. Surgery for gastric cancer in the form of total or distal gastrectomy is definitive treatment. Feeding jejunostomy (FJ) though improves postoperative nutritional status and outcome, it is not devoid of its complications. In this study, we present the outcomes of nasojejunal (NJ) feeding and FJ and complications associated with them.Materials and Methods It is both retrospective and prospective observational study in patients with gastric cancer undergoing surgery. Patients were divided into two groups: those who underwent FJ and those who underwent NJ route of feeding placed intraoperatively.Results A total of 279 patients of gastric cancer who underwent surgery were taken into study, of which, 165 were male and 114 females. FJ was done in 42 and NJ in 237 patients, respectively. Gastrectomy + NJ was done in 128 patients, gastrectomy + FJ in 27 patients, gastrojejunostomy + NJ in 109 patients, and FJ in 15 patients. We had three patients of bile leaks in FJ group, of which one patient had intraperitoneal leak who needed re-exploration; rest of the two had peri-FJ external leaks, who were managed conservatively. Most of the complications of NJ group were minor.Conclusion Our study of 279 patients in gastric cancer has shown that FJ is sometimes associated with major complications with increased hospital stay and morbidity when compared with NJ tube feeding without any difference in nutritional outcomes. Hence, NJ route of postoperative enteral nutrition can be considered as an alternative to FJ wherever feasible in view of its technical safety and minor complications and morbidity.
Keywords: complications; feeding jejunostomy; gastric cancer; nasojejunal feeding